SHOOT MULTIPLICATION AND PLANT REGENERATION FROM IN VITRO CULTURES OF DRUMSTICK TREE (Moringa oleifera Lam.) - Hai Chau, Mai; Minh Quang, Nguyen (Journal of Forestry Science and Technology, 2019)
To obtain plantlets of drumstick tree (Moringa oleifera Lam.) with identical genetic make up for propagation or field production, in vitro cultures of drumstick tree were produced. For multiple of shoot induction, the stem explants of drumstick tree plantlets were cultured on Murashige and Skoog (MS) agar medium supplemented with different concentrations of 6-benzyl adenine purine (BAP) and maintained at 25 ± 2°C for 5 weeks. The results showed that sterilization with 0.1% HgCl2 solution for 8 minutes gave a clear explant rate of 53.3% and a germination rate of 51.7%. Multiple of shoot induction was present in the stem explants that were cultured on the MS medium supplemented with BAP at the concentration range of 0.5 - 3.0 mg/l or the combination of BAP at 1.5 mg/l, TDZ at the range of 0.2 - 1.0 mg/l and NAA at the range of 0.2 - 1.0 mg/l. The MS medium containing BAP at 1.5 mg/l was found to produce 95.3% shoot formation with the highest average number of 8.4 shoots per explant. For plant regeneration, the shoot explants were cultured on ½ MS + 7 g/l agar + 15 g/l sucrose supplemented with IBA and IAA at difference concentration root induction. The results showed that ½ MS + 7 g/l agar + 15 g/l sucrose supplemented with IBA at 0.3 mg/l and IAA at 0.2 mg/l produce 100% root formation with the highest average number of 4.2 roots per explant and 3.5 cm in length. Tissue culture protocol reported in this study is an alternative means of micropropagation of drumstick plantlets with uniform genotypes for breeding selection and field production.